Complex evaluation of the economic crisis impact on Lithuanian industries - Krivka, Algirdas (Journal of Business Economics and Management, 2014)
The paper analyses the impact of the economic crisis of 2008 on Lithuanian industries. The research involves 68 industries identified according to the 2nd-digit level classification of economic activities by Statistics Lithuania. Considering industry to be a complex phenomenon, the crisis effect is evaluated complexly on the basis of the system of 10 financial state and performance indicators belonging to four main groups of enterprise financial ratios: profitability, liquidity, solvency and asset turnover. SAW, TOPSIS and VIKOR multi-criteria decision making methods, widely applied in construction, economics and management, are selected as mathematical tools for quantitative assessment of the economic crisis effect on Lithuanian industries. By applying multi-criteria decision making methods relative positions (ranks) of industries are determined for every year of the period of 2006–2011. The ranks and their changes are further analysed distinguishing pre-crisis, crisis, and post-crisis periods, determining the industries most and least affected by the economic crisis; also, the industries characterised by the fastest and the slowest after-crisis recovery.